Health Promotion Strategy Analysis According to WHO to Improve Clean and Healthy Living Behaviors in Working Area of UPTD Puskesmas Plosoklaten Kediri Regency - Kharisma Ardy Pradana; Ratna Wardani; Hengky Irawan (STRADA : Jurnal Ilmiah Kesehatan, 2025)
This study employed a quantitative approach with a cross-sectional design. The population included all residents domiciled in the working area of UPTD Puskesmas Plosoklaten, Kediri Regency, totaling 28,000 individuals. The sample size consisted of 400 respondents. Data were collected using a questionnaire and analyzed using multiple linear regressions. Findings revealed that out of 400 respondents, nearly half assessed advocacy as moderate (182 respondents, 45.5%), nearly half evaluated social support as good (159 respondents, 39.8%), nearly half perceived community empowerment as moderate (188 respondents, 47.0%), and nearly half reported good PHBS practices (197 respondents, 49.3%).